2019
DOI: 10.1002/rcs.1990
|View full text |Cite
|
Sign up to set email alerts
|

Robotics‐assisted versus conventional manual approaches for total hip arthroplasty: A systematic review and meta‐analysis of comparative studies

Abstract: Background Several studies have compared robotics‐assisted (RA) and conventional manual (CM) approaches for total hip arthroplasty (THA), but their results are controversial. Methods A literature search was conducted for controlled clinical trials (CCTs) comparing the clinical efficacy of the RA and CM approaches for THA and published between August 1998 and August 2018. The obtained data were analyzed using the statistical software Review Manager 5.3. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 42 publications
3
53
0
Order By: Relevance
“…Similarly, in a prospective matched cohort of 50 patients undergoing conventional manual THA and 25, a Mako TM robotic-arm assisted THA, Kayani et al [50] also reported improved accuracy placement of the cup according to the Lewinnek and Callanan safe zone. Recent studies reported similar results [51][52][53][54][55][56].…”
Section: Surgical Proceduressupporting
confidence: 62%
See 1 more Smart Citation
“…Similarly, in a prospective matched cohort of 50 patients undergoing conventional manual THA and 25, a Mako TM robotic-arm assisted THA, Kayani et al [50] also reported improved accuracy placement of the cup according to the Lewinnek and Callanan safe zone. Recent studies reported similar results [51][52][53][54][55][56].…”
Section: Surgical Proceduressupporting
confidence: 62%
“…However, there was no difference between the different groups considering the technical problems (1 case was secondary to poor fixation of the femoral landmark in group A, 1 case of bad impaction of the cup in group A) or complications. In a recent meta-analysis, Han et al [53] reported a significantly increased operating time of robotic procedures compared to the conventional techniques. This learning curve has to integrate sometimes the adjustment of surgeon practice with the use of a new design of the implant.…”
Section: Management Of Hip Offset and Hip Center Of Rotationmentioning
confidence: 99%
“…Xu et al [16] reported operation time was increased 19.2 minutes by the use of the large console navigation system in their meta-analysis. And recent meta-analysis reported operation time was increased 20.72 minutes by the use of the robotic system [29]. Recently, one study reported the results of HipAlign in the supine position [23].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that gait asymmetry was not fully eliminated by either robotic arm–assisted or freehand THA. A previous study indicated that robotic arm–assisted THA is associated with better radiological outcomes and fewer intraoperative complications, but similar functional scores …”
Section: Discussionmentioning
confidence: 93%
“…A previous study indicated that robotic arm-assisted THA is associated with better radiological outcomes and fewer intraoperative complications, but similar functional scores. 27 Internal rotation gait has been previously reported in children with excessive femoral anteversion as an adaptation to decreased abductor capacity. 28 Higher internal rotation of the native hip was also found in patients with groin pain and impingement and correlated with bony anatomy in the axial plane.…”
Section: Discussionmentioning
confidence: 94%